Analisis Komprehensif Lafaz Sharih Dan Kinayah: Makna, Penerapan Dalam Nash, dan Implikasi Hukumnya - Haq, Fitri Maylan; F, Fatmawati; Amin, Abd. Rauf (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The application of sharih and kinayah lafaz requires in-depth study because current developments require a re-examination of the meanings of lafaz in sharia texts so that they remain relevant to societal conditions, therefore this paper discusses the study of lafaz in terms of the use of sharih and knayah meanings. To obtain relevant research results, this research uses data collection techniques or literature study methods. The results of this research are that sharih and kinayah lafaz have contradictory meanings and applications, where sharih lafaz is a lafaz whose pronunciation and application is clear, does not require explanation and is not accompanied by intention, for example if the husband says